ANALYSIS OF FINANCIAL STATEMENTS TO ASSESS FINANCIAL PERFORMANCE AT PT. PEGADAIAN (Persero) BULUKUMBA BRANCH - Nurfadillah, Nurfadillah; Nasrullah , Nasrullah; Sahrullah, Sahrullah (CV. AFDIFAL MAJU BERKAH, 2024)
This research is descriptive quantitative research with the aim of knowing the financial performance of PT. Pegadaian (Persero) Bulukumba Branch for the 2020-2022 period using liquidity, solvency, profitability and activity ratios. This sample was taken from PT. Pegadaian (Persero) Bulukumba Branch in the form of financial reports for the period 2020 to 2022. The data collection method was carried out using observation and documentation techniques. The research results seen from the liquidity ratio show that the Company's financial performance is in good condition because the Company is able to pay its current obligations on time. Judging from the solvency ratio, the company's financial performance is in poor condition due to the large amount of debt used compared to the current assets owned. Judging from the profitability ratio, the company's financial performance is in poor condition, this is because although it has increased every year, it is still below industry standards. Judging from the activity ratio, the company's financial performance is in poor condition, this is because the increase in income is smaller than the increase in total assets.